2021
DOI: 10.1038/s41598-021-87832-5
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study on the indirect effect of sulfate on the summer climate over the eastern China monsoon region

Abstract: In this study, we designed a sensitivity test using the half number concentration of sulfate in the nucleation calculation process to study the aerosol-cloud interaction (ACI) of sulfate on clouds, precipitation, and monsoon intensity in the summer over the eastern China monsoon region (ECMR) with the National Center for Atmospheric Research Community Atmosphere Model version 5. Numerical experiments show that the ACI of sulfate led to an approximately 30% and 34% increase in the cloud condensation nuclei and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Using Community Atmosphere Model 3.0, some scholars found a seasonal effect of sulfate aerosols on the water cycle process (Wu and Liu, 2009). Some scholars have also noted that since the late 1970s, the increase in anthropogenic sulfate aerosols has led to the weakening of summer monsoon precipitation in East Asia (Wang et al, 2021)…”
Section: Estimation Of Nanoparticle Content and Its Impact The Global...mentioning
confidence: 99%
“…Using Community Atmosphere Model 3.0, some scholars found a seasonal effect of sulfate aerosols on the water cycle process (Wu and Liu, 2009). Some scholars have also noted that since the late 1970s, the increase in anthropogenic sulfate aerosols has led to the weakening of summer monsoon precipitation in East Asia (Wang et al, 2021)…”
Section: Estimation Of Nanoparticle Content and Its Impact The Global...mentioning
confidence: 99%
“…Using Community Atmosphere Model 3.0, some scholars found a seasonal effect of sulfate aerosols on the water cycle process (Wu and Liu, 2009). Some scholars have also noted that since the late 1970s, the increase in anthropogenic sulfate aerosols has led to the weakening of summer monsoon precipitation in East Asia (Wang et al, 2021)…”
Section: Estimation Of Nanoparticle Content and Its Impact On The Glo...mentioning
confidence: 99%
“…The Beijing-Tianjin-Hebei (BTH) region, recognized as China's capital economic zone, is rapidly urbanizing and industrializing. Sulfate aerosol is one of the predominant summer aerosol components in the BTH region [1][2][3] . The primary source of atmospheric sulfate is the oxidation of SO2, which mainly emanates from human activities, industrial processes, and the combustion of fossil fuels 4 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance,Wang et al (2021) observed sulfate aerosols acted as CCN, increasing the CCN and cloud droplet number concentrations by approximately 30% and 34%, respectively, during summer in the East Asian monsoon region. This reduced the effective radius of cloud droplets below 850 hPa by 4%, and increased the total liquid water path by 11%, which caused a decline in the radiation reaching the surface, consequently cooling the atmosphere.…”
mentioning
confidence: 98%
See 1 more Smart Citation